Study about Rapid Diagnosis of Pulmonary Tuberculosis in Sputum Cytology - Rajat Kumar; Khushbu Kumari; K. D. Kulkarni; S. S. Hiremath; M. H. Prabhu (Advanced Research in Biological Science Vol. 1, 2023)
This chapter evaluate the diagnostic utility of Pap stain, Auramine-O and ZN stain in rapid diagnosis of pulmonary tuberculosis in sputum cytology. Mycobacterium Tuberculosis (MTB) is most common communicable disease in low socioeconomic population. It is most common in developing countries like India. Study was done on Sputum of clinically suspected case of pulmonary tuberculosis from June 2017 to August 2017. On all received sample Z N, Pap, Auramine-O staining done. Among clinically suspected 150 patients. Tuberculosis was diagnosed in 74 patients. Pap shows 49 (66.21%), Auramine-O shows 42(56.75%); ZN shows 35 (47.29%) cases positive. Tuberculosis commonly affects lungs but can also be extra-pulmonary. Hence microscopic examination of sputum for detection of Acid Fast Bacilli (AFB) is of utmost importance. Early detection can prevent further complication. The method used in the present study enables in rapid identification of these infective sources and hence prevent further transmission and is thus important in TB control. The primary indicators that a person may have tuberculosis include an evening increase in temperature, weight loss, a cough lasting longer than two weeks, and CXR results. In the case of patients who are seropositive, males are more affected than females. When using fluorescent microscopy to diagnose pulmonary tuberculosis, Pap is marginally more sensitive than Auramine-O.